Principles of Selective Immigration Policy in Relation to Visa Free Entry for Tourism Purposes - Anak Agung Gede Duwira Hadi Santosa; I Made Marta Wijaya; Ni Luh Dewi Sundariwati (Badan Strategi Kebijakan Hukum, 2022)
Tourism has an important role in enhancing the economic growth of a country. As a country with growing tourism industry, Indonesia is trying to increase foreign tourist visits by rolling out a visa-free policy. However, the visa-free policy has not yet fully provided benefits. In practice, this policy triggers the occurrence of transnational and international crimes, the rise of illegal foreign workers and the large number of foreigners who abuse their residence permits. The purpose of this research is to analyze the visa-free policy from the perspective of selective policy theory. The research method is normative legal research with a statutory approach and a conceptual approach. The results of the study show that the visa-free policy as contained in Presidential Regulation Number 21 of 2016 is not fully based on the theory of selective policy. In conclusion, the visa-free policy cannot be implemented optimally because the formulation of this policy does not represent the theory of selective policy. Consequently, the implementation of visa-free policy generates various matters that have an adverse impact on Indonesia. In order to overcome this problem, it is urgent to evaluate and improve the visa-free policy and to make this policy truly based on the theory of selective policy. Thus, the visa-free policy will be very selective in choosing and determining countries that can receive a visa-free policy.